Big Character Posters in China: A Historical Survey - Sheng, Hua (Columbia Journal of Asian Law, 1990)
During the past fifty years, the writing of big character posters (dazibao) has emerged as a principle form of political expression in the People’s Republic of China (PRC). Dazibao have accompanied nearly every major political movement in the PRC. In China, where the state exercises a complete monopoly over the means of communi- cation, dazibao have proven particularly significant because of their impact on the PRC’s political leadership. In a society that prizes rep- utations, outward appearances, and conformance with social norms, dazibao create a public spectacle, the very existence of which implies that the leadership has failed and that the community is disaffected. Moreover, dazibao reach a relatively wide audience at minimum cost and provide some anonymity for the writer. Because of these unique characteristics dazibao represent one of the few effective vestiges of free speech that may be used to voice political dissent in China.